2017
DOI: 10.1038/s41598-017-11679-y
|View full text |Cite
|
Sign up to set email alerts
|

Electroretinography Reveals Difference in Cone Function between Syndromic and Nonsyndromic USH2A Patients

Abstract: Usher syndrome is an inherited and irreversible disease that manifests as retinitis pigmentosa (RP) and bilateral neurosensory hearing loss. Mutations in Usherin 2A (USH2A) are not only a frequent cause of Usher syndrome, but also nonsyndromic RP. Although gene- and cell-based therapies are on the horizon for RP and Usher syndrome, studies characterizing natural disease are lacking. In this retrospective analysis, retinal function of USH2A patients was quantified with electroretinography. Both groups had marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 49 publications
3
22
0
Order By: Relevance
“…In both ush2a mutants, however, we observed impaired ERGs at 5 dpf, which is suggestive of early-onset cone dysfunction. Although ERG data of pre-symptomatic patients are typically not available, a recent study demonstrated markedly reduced ERG responses for both rods and cones in adolescent Usher syndrome type 2a patients (Sengillo et al, 2017), consistent with our observations of cone defects by the onset of vision in zebrafish ush2a mutants. Furthermore, USH2A -associated retinal degeneration in humans has a slow, progressive pathology.…”
Section: Discussionsupporting
confidence: 90%
“…In both ush2a mutants, however, we observed impaired ERGs at 5 dpf, which is suggestive of early-onset cone dysfunction. Although ERG data of pre-symptomatic patients are typically not available, a recent study demonstrated markedly reduced ERG responses for both rods and cones in adolescent Usher syndrome type 2a patients (Sengillo et al, 2017), consistent with our observations of cone defects by the onset of vision in zebrafish ush2a mutants. Furthermore, USH2A -associated retinal degeneration in humans has a slow, progressive pathology.…”
Section: Discussionsupporting
confidence: 90%
“… 13 As anticipated in a rod-cone dystrophy, cone responses to LA 3.0 flicker ERG were less affected and remained measurable in the majority of participants at all ages. Similar to other studies, 16 the ARRP group had significantly larger LA 3.0 flicker ERG amplitudes than the USH2 group despite being older on average. In a multivariate analysis, no participant characteristic other than clinical diagnosis was associated with LA 3.0 flicker ERG amplitude.…”
Section: Discussionsupporting
confidence: 88%
“…Of note, the USH2A patient cohort included patients with both arRP and Usher syndrome type 2. The findings of a previous study, which suggest that cone function as measured by 30 Hz ERG is higher in non-syndromic as compared to syndromic USH2A patients 19 , may account for Sandberg et al .’s observation that the loss of 30 Hz ERG function was faster in USH2A patients compared to RPGR .…”
Section: Discussionmentioning
confidence: 81%